A Blueprint of Leadership Development for Female Marriage Migrants: A Pilot Exploration in Taiwan. Issue 4 (November 2022) - Han, Pi-Chi
In 2020, more than 560, 617 female marriage migrants (FMMs) live in Taiwan. For over three decades, they have been victims of social, gender, and cultural discrimination and have been considered as an inferior group of "desirable others" from "undeveloped countries." Until today, literature about FMMs has focused on the problems and challenges they encountered, whereas there is no literature on their leadership development (LD) in Taiwan. By exploring 10 FMM leaders and their LD, this study charts their journey to success. The research has the following aims: (a) to explore life experiences as a pathway to LD, (b) to find an LD blueprint for FMMs, and (c) to bridge the literature gap for FMMs' LD and provide implications to adult learning (AL) and human resources development (HRD) practitioners in planning and conducting training programs for FMMs' LD. The theory of transformative learning (TTL) was applied as a theoretical framework whereas the qualitative research design was utilized as the methodology to explore 10 FMM leaders in Taiwan. The LD blueprint was built with seven themes derived from individual interviews and three themes from the focus group discussion. Resilience was found as the salient marker of building a successful mental model in FMMs' LD. Implications are provided.